The importance of time in nutrient regulation: a case study with spotted-wing Drosophila (Drosophila suzukii) - Deans, Carrie; Hutchison, William (Frontiers in Insect Science, 2023)
The ability of living things to acquire the nutrients needed to carry out required physiological functions has important consequences for fitness. However, an organism must not simply meet the requirements for individual nutrients, but must ingest an optimal balance of multiple nutrients. Despite this, animals rarely consume truly balanced resources, and instead commonly feed selectively across multiple unbalanced resources to reach an optimal balance, i.e., intake target. Nutritional research has predominantly focused on the behavioral strategies employed during nutrient regulation, as well as the fitness consequence of failing to meet intake targets, but little work has been done on the temporal aspects of this process. For instance, within what timeframe must organisms reach their intake target before a fitness cost is incurred? Hours, days, weeks? In this study, we investigated how nutrient regulation interval impacts consumption and performance in adult female spotted-wing Drosophila (Drosophila suzukii). Females were allowed to feed on either a protein- or a carbohydrate-biased diet over different time intervals (8-, 16-, 32-, 48- and 64-hr), while control flies were constrained to one of these diets or a diet with an optimal macronutrient ratio (1:3). We also tested the importance of switching schedule (16a- and 16b-hr) by altering the timing of the switch within the same interval. Regulation interval had a significant impact on feeding behavior and consumption. Total consumption was highest on the shorter-interval treatments (8-, 16a-, and 16b-hr) and declined as the interval period increased. The relative consumption of both diets was statistically-different across intervals and was higher for the carbohydrate-biased diet. Consumption of the protein-biased diet was more variable and differed significantly across the 16a- and 16b-hr treatments, indicating that the timing of diet switches can impact feeding behavior. Performance data showed that shorter regulation intervals led to longer fly lifespans in ways that mirrored the impact of diet macronutrient ratio on lifespan. These results show that regulation intervals, as well as the timing of diet changes, can have strongly impact feeding behavior, nutrient regulation, and fitness. This has important implications for processes affecting host phenology and/or resource distribution, such as global climate change.